Nuclear receptor coactivator‐6 is essential for the morphological change of human uterine stromal cell decidualization via regulating actin fiber reorganization. Issue 4 (5th April 2022) - Watanabe, Norikazu; Kawagoe, Jun; Sugiyama, Akiko; Takehara, Isao; Ohta, Tsuyoshi; Nagase, Satoru
Abstract: Nuclear receptor coactivator 6 (Ncoa6), a modulator of several nuclear receptors and transcription factors, is essential for the decidualization of endometrial stromal cells in mice. However, the function of Ncoa6 in the human endometrium remains unclear. We investigated its function in the decidualization of human endometrial stromal cells (HESCs) isolated from resected uteri. Knockdown of Ncoa6 was performed using two independent small interfering RNAs. Decidualization was induced in vitro via medroxyprogesterone and cyclic adenosine monophosphate. We compared decidualized cellular morphology between the Ncoa6 knockdown cells and control cells. Messenger RNA (mRNA) sequencing was performed to determine the Ncoa6 target genes in undecidualized HESCs. We found that the knockdown of Ncoa6 caused the failure of morphological changes in decidualized HESCs compared to that in the control cells. mRNA sequencing revealed that Ncoa6 regulates the expression of genes associated with the regulation of actin fibers. Ncoa6 knockdown cells failed to reorganize actin fibers during the decidualization of HESCs. Ncoa6 was shown to play an essential role in decidualization via the appropriate regulation of actin fiber regulation in HESCs. Herein, our in vitro studies revealed a part of the mechanisms involved in endometrial decidualization. Future research is needed to investigate these mechanisms in women with implantation defects. Abstract : Human endometrial stromal cells (HESCs) transfected with nontarget small interfering RNA (siRNA) (control) showed the typical cobblestone pattern of decidualized endometrial stromal cells after medroxyprogesterone acetate (MPA)/cyclic adenosine monophosphate (cAMP) treatment. Decidualized HESCs transfected with nuclear receptor coactivator 6 (Ncoa6)‐specific siRNAs (Ncoa6 knockdown) showed spindle shape even after MPA/cAMP treatment.